Towards a multi-agent Clinical Trial Center framework to support modern clinical trials - Bjorn Redfors; Weishen Pan; Chen Lyu; Mario Gaudino; Fei Wang; Hua Judy Zhong (npj Digital Medicine, 2026)
Abstract Clinical Trial Centers (CTCs) manage complex multi-site trials under rising regulatory and operational demands. Traditional workflows are labor-intensive and error-prone. Existing AI handles narrow and siloed tasks. We introduce Agent System for TRial Automation (ASTRA), a proposed multi-agent CTC in which a central Coordinator Agent and site-level Agents orchestrate domain-specialized AI-agent teams under human supervision. In this framework, agents follow standard messaging using shared environments and a version-controlled knowledge base. This manuscript introduces ASTRA as a design framework and summarizes key implementation and regulatory challenges for this hybrid automation-plus-oversight model.